1992
DOI: 10.1128/jb.174.6.2032-2038.1992
|View full text |Cite
|
Sign up to set email alerts
|

Localization of diphtheria toxin nuclease activity to fragment A

Abstract: ). Here we show that (i) trypsinization of DTx does indeed produce nucleolytically active DTA, (ii) reduction of electroeluted, unreduced, cleaved DTx (58 kDa) yields nuclease-active DTA (24 kDa), and (iii) fractionation of DTx and DTA by anion-exchange chromatography leads to coelution of nuclease activity with both forms of the toxin, even though each form elutes at a distinct salt concentration. In addition, we show that Escherichia coli-derived DTA also expresses nuclease activity. These studies confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
5
11
0
1
Order By: Relevance
“…Cell lysates treated with diphtheria toxin were used to measure the enzymatic activity (FA~ 10 ng) for ADP-ribosylation of eEF2 (20 pmol). Deoxyribonuclease activity DT and FA have been repeatedly shown to possess deoxyribonuclease activity [23,24]. These findings were confirmed in the present study as assayed by changes in hyperchromicity.…”
Section: Cellular Interactions Of Fasupporting
confidence: 80%
“…Cell lysates treated with diphtheria toxin were used to measure the enzymatic activity (FA~ 10 ng) for ADP-ribosylation of eEF2 (20 pmol). Deoxyribonuclease activity DT and FA have been repeatedly shown to possess deoxyribonuclease activity [23,24]. These findings were confirmed in the present study as assayed by changes in hyperchromicity.…”
Section: Cellular Interactions Of Fasupporting
confidence: 80%
“…We found that for both CRM197 and DTx, Ca 2+ and Mg 2+ promote single-strand nicks, whereas Mn 2+ promotes doublestrand breaks ( Figure 7B). 4 These findings are similar to X-ray findings with bovine pancreatic DNase I:DNA cocrystals (23). With ssDNA, Mn 2+ leads to no increase in cleavage rate over that seen with Ca 2+ and Mg 2+ (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…4 Moreover, in a yeast expression system, the level of EF-2 available for ADP-ribosylation did not change with time, regardless of whether DTM was expressed at 18 or 30°C. 3 We conclude from these observations that DTM's temperature-sensitive cytotoxic effects in yeast and Drosophila are not the result of low-temperature-acquired ADPrT activity.…”
Section: Resultsmentioning
confidence: 98%
“…The deoxyribonuclease activity in C. diphtheriae and C. ulcerans has been described in the literature for many decades (Messinova et al 1963;Barksdale 1970;Chang et al 1989;Lessnick et al 1992;Lee et al 2005). Toxigenic and nontoxigenic C. diphtheriae were found to be equally proficient at producing deoxyribonuclease (Barksdale 1970; Groman and Dean 1973).…”
Section: Discussionmentioning
confidence: 99%